Disain Sistem Navigasi Automatic Identification System (AIS) Transceiver Berbasis Mini Computer Pada Kapal Nelayan Tradisional Di Madura - Akh. Maulidi (INOVTEK POLBENG, 2019)
Navigation system is the key of ship safety in sailing. Automatic Identification System (AIS) is a navigation system used in Vessel Traffic Services (VTS) to identify and exchange data electronically. The International Maritime Organization (IMO) and the 1974 International Convention for the Safety of Life on the Sea (SOLAS) and Colreg (1972 collision regulation) require AIS to be installed in ships that have a gross tonnage (GT) of 300 tons or more and for all types of passenger vessels.AIS can replace a number of other communication tools that have been used such as compass, maps, radar and GPS. However, the function and practicality that is owned is comparable to the very expensive price so that traditional fishermen cannot reach the expensive price. From this, researchers are looking for other alternatives that can be a solution to get a cheap and reliable navigation system.By General Purpose Output Input (GPIO) pin on Mini PC, it can receive Input and expend output based on instructions given directly or using Web Server. Besides, mini PC has very cheap price compared to similar devices. By providing algorithm program on a mini PC, it can be used as an AIS Transceiver to send ordinate, speed, and direction of ship movement ship. Thus, help traditional fishing boats in Madura to obtain their navigation system.